استثمار القيمة التعبيرية للحرف في التفسير الإشاري عند ابن القيم رحمه الله - حذيق, العيد (جامعة الوادي - University of Eloued, 2019)
هذا المقال بعنوان: استثمار القيمة التعبيرية للحرف في التفسير الإشاري عند ابن القيم رحمه الله؛ وهو يُعالجُ إشكاليَّةَ توظيف علماء الأمَّة الإسلاميَّة الموسوعيين - وابن القيِّم رحمه الله نموذجٌ عنهم -، لعناصرَ غيرِ تقليديَّة في عمليَّة تفسير القرآن الكريم. وقد سلكتُ لمعالجة هذا الإشكال خطَّةً من مقدِّمةٍ وثلاثة مطالب وخاتمةٍ. بيَّنتُ في المقدِّمةِ الإشكال الَّذي يطرحه الموضوع، وأهميته، والأهداف المرجوة من دراسته، والخطة المطروقة لمعالجته. أمَّا المقصد الأول؛ فكان لبيان المقصود من القيمة التعبيرية للحرف، فيما جعلنا المقصد الثَّانيَ لتحديد ماهية التفسير الإشاري، وضوابط الأخذ به، وكان المقصدُ الثَّالثُ تطبيقًا عمليًّا لاستثمارِ ابن القيم رحمه الله لهذه القيمة في التفسير. وقد توصَّلت في هذا البحث إلى نتائج أهمُّها: أنَّ لابن القيِّم رحمه الله حِسًّا لُغويًّا دقيقًا؛ تنبَّه من خلاله لتوظيف عناصر تبدو لأول وهلةٍ بعيدةً عن التفسير. وأنَّ في التفسير الإشاريِّ إلماحاتٍ هاديةً إذا كانت منضبطةً بالضوابطِ الشرعيَّةِ. Abstract: This article entitled "The Investment of the Expressive Value of the Letter in the Sign Interpretation" of Ibn Al Qayyim (May Allah Have Mercy on Him) deals with the issue of the use of non-traditional elements by the scholars of the Islamic Ummah (taking Ibn Al Qayyim as a model) in the process of interpreting the Holy Quran. To treat this issue , I have made a plan of an introduction , three chapters, and a conclusion . In the introduction , I explain the problem that the subject poses, its importance , the aim of studying it , and the plan set to address it. The first chapter is to explain the meaning of the expressive value of the letter , while the second chapter is to determine what is the sign interpretation and he regulations of its acceptance. The third chapter is a practical application of Ibn Al Qayyim's ( May Allah Have Mercy on Him) investment of this value in the process of interpretation. Through this research, I have reached some conclusions; most importantly : Ibn Al Qayyim had a precise linguistic sensitivity through which he was alerted to the use of elements that ,at first glance, seem far from interpretation. Moreover, there are guiding allusions in the sign interpretation if they were regulated by the Shari'a rules. key words: Ibn Al Qayyim, Expressive Value of the Letter, Sign Interpretation.
مقال
Keywords: التفسير ; القيمة التعبيرية ; الحرف العربي ; ابن القيم ; الإشارات